PENGARUH PERTUMBUHAN BIAYA PRODUKSI DAN BIAYA PROMOSI TERHADAP PERTUMBUHAN LABA BERSIH DAN PENJUALAN - Muhammad Ariz Al Warits; Dikdik Saleh Sadikin (Ibs Press, 2023)
This study aims to find out above the relationship between Production Cost and Promotion Costs on Net Profit and Sales. This study used data from 26 companies in various industrial sectors listed on the Indonesia Stock Exchange. The sampling technique in this study uses a purposive sampling technique with predetermined criteria. The research method used in this research is multiple linear regression analysis technique using E-views 9 software. The results of this study show that the growth of Production Cost and promotion costs does not affect the growth of the net profit. However, Production Cost Growth has a positive effect on sales Growth and Promotion Cost Growth has no effect on Sales Growth.